2019
DOI: 10.24093/awej/call5.14
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Perception about Integrating Blended Learning in ELT

Abstract: The study highlights English a Foreign Language (EFL) learners' perceptions about integrating Blended Learning (BL) to facilitate them completing their foundation year English courses at a Saudi university. The focus of the study was to investigate "the EFL learners' perception about integrating blended learning in their English Language Teaching (ELT) process". For this purpose, a survey was constructed in three subsections investigating the learners' viewpoints about BL as a platform: a) to improve learners'… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
5
16
0
Order By: Relevance
“…Similar results were found by Alsowayegh et al (2019) who reported that students were motivated to search other social media accounts, and was also found by Al Bataineh et al (2019) who reported that blended learning improved students' digital skills. This result was also confirmed by other researchers (Bukhari & Basaffar, 2019;Hamad, 2017) who found that students were motivated to learn independently. Implementation of blended learning to deliver English classes fitted well with students' circumstances.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 87%
See 4 more Smart Citations
“…Similar results were found by Alsowayegh et al (2019) who reported that students were motivated to search other social media accounts, and was also found by Al Bataineh et al (2019) who reported that blended learning improved students' digital skills. This result was also confirmed by other researchers (Bukhari & Basaffar, 2019;Hamad, 2017) who found that students were motivated to learn independently. Implementation of blended learning to deliver English classes fitted well with students' circumstances.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 87%
“…It also proves that online tests have had a positive impact on improving the students' punctuation, spelling and grammar skills. This result adds to the string of findings that blended learning supports EFL students' language skills (Al Bataineh et al, 2019;Alsowayegh et al, 2019;Bukhari & Basaffar, 2019;Gulnaz et al, 2020) and the finding of Al-Qahtani (2019) who reported that virtaul classes enhanced the language learners' communicative skills. This result also corresponds with the result from Alowedi (2020), who found that blended learning provides additional learning opportunities to EFL students.…”
Section: Research Question 1: What Are the Benefits Of Implementing Bsupporting
confidence: 70%
See 3 more Smart Citations